Fengycin C produced by Bacillus subtilis EA-CB0015 (2014)
Bacillus subtilis EA-CB0015 was isolated from the phyllosphere of a banana plant and tested for its potential to produce bioactive compounds against Mycosphaerella fijiensis -- Using a dual plate culture technique the cell-free supernatant of B. subtilis EA-CB0015 produced inhibition values of 89 ± 1% -- The active compounds were purified by solid-phase extraction and HPLC, and their primary structures determined using mass spectrometry and amino acid analysis -- A new fengycin isoform, fengycin C, with the amino acid sequence Glu-Orn-Tyr-Thr-Glu-Val-Pro-Gln-Thr-Ile was isolated -- The peptidic moiety differs from fengycin B at position 9 and from fengycin A at positions 6 and 9 -- The β-hydroxy fatty acyl chain is connected to the N-terminal of the decapeptide and can be saturated or unsaturated, ranging from 14 to 18 carbons -- The C-terminal residue of the peptidic moiety is linked to the tyrosine residue at position 3, forming the branching point of the acyl peptide and the eight-membered cyclic lactone